2015
DOI: 10.1155/2015/562345
|View full text |Cite
|
Sign up to set email alerts
|

Antifatigue Activity of Liquid CulturedTricholoma matsutakeMycelium Partially via Regulation of Antioxidant Pathway in Mouse

Abstract: Tricholoma matsutake has been popular as food and biopharmaceutical materials in Asian countries for its various pharmacological activities. The present study aims to analyze the antifatigue effects on enhancing exercise performance of Tricholoma matsutake fruit body (ABM) and liquid cultured mycelia (TM) in mouse model. Two-week Tricholoma matsutake treatment significantly enhances the exercise performance in weight-loaded swimming, rotating rod, and forced running test. In TM- and ABM-treated mice, some fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 44 publications
(46 reference statements)
2
24
0
Order By: Relevance
“…The WLFST is used to evaluate the anti-fatigue effect of PAE, and the experiment was performed as described previously [55]. The mice were individually placed into the plastic pool (30 cm × 35 cm × 60 cm) containing freshwater (23 ± 1 • C), approximately 50 cm deep.…”
Section: Weight-loaded Forced Swimming Testmentioning
confidence: 99%
“…The WLFST is used to evaluate the anti-fatigue effect of PAE, and the experiment was performed as described previously [55]. The mice were individually placed into the plastic pool (30 cm × 35 cm × 60 cm) containing freshwater (23 ± 1 • C), approximately 50 cm deep.…”
Section: Weight-loaded Forced Swimming Testmentioning
confidence: 99%
“…We have studied the pharmacological activities of TM for years and confirmed that TM possesses antifatigue effects related to the modulation of AMPK linked antioxidation pathway [25]. Recently, our data show that TM strongly enhances immunity of cyclophosphamide-induced immunosuppressed mouse models associated with nuclear factor kappa B signaling.…”
Section: Discussionmentioning
confidence: 64%
“…Fatigue can therefore be divided into two categories: Physical and mental fatigue. Physical fatigue is the inability of a muscle to maintain normal movement (2), which may induce a heightened stress response, endocrine dyscrasia, immune dysfunction and organ injury (3).…”
Section: Introductionmentioning
confidence: 99%
“…Various species of fungi and certain herbs may postpone the onset of fatigue, improve athletic ability and enhance the elimination of fatigue-related metabolites (13). The anti-fatigue effects of Tricholoma matsutake, Cordyceps militaris and Antrodia cinnamomea in murine models have been examined in previous studies by assessing their effect on oxidative stress (3,14,15). Tuber melanosporum (TM), a fungus containing unique bioactive metabolites, contains important nutrients including proteins, unsaturated fatty acids, amino acids, sphingolipids, cerebrosides and polysaccharides (16).…”
Section: Introductionmentioning
confidence: 99%